(untitled photo) - Morrell, Amish (UnderCurrents: Journal of Critical Environmental Studies, 1994)
Amish Morrell is a student in the Bachelors of Environmental Studies program at York University. He is exploring the use of photography in facilitating awareness of and communication around environmental issues. Amish is from Cape Breton, nova Scotia.